incidencia de la inteligencia artificial en la producción de contenidos audiovisuales en la ciudad de machala - Chica Parraga, Andy Jahir (Machala, 2025)
Currently, the production of audiovisual content is being transformed due to artificial intelligence, optimizing technical processes and enhancing creativity. However, its implementation presents ethical challenges such as resistance to change, technical limitations, and the belief that AI will replace job roles. This is false, as AI would serve as a complement, requiring professionals in the field who can adapt to the constant changes in the audiovisual industry. This research aims to analyze the impact of artificial intelligence on audiovisual content production by exploring which tools are used and how they are transforming the stages of pre-production, production, and post-production. This allows for identifying the opportunities AI offers to improve processes, as well as examining the challenges and limitations that arise in its implementation. Additionally, it encourages reflection on the future of the industry and helps determine the skills and knowledge necessary to adapt and make the most of these technologies. The findings highlight that, while AI brings significant benefits, such as time optimization, cost reduction, and creativity enhancement, its incorporation also presents important challenges. These include the learning curve, the need for continuous training, investment in premium tools, and ethical concerns related to content accuracy and its impact on employment.
En la actualidad la producción de contenidos audiovisuales está siendo transformada debido a la inteligencia artificial, optimizando los procesos técnicos y potenciando la creatividad. Aun así, su implementación presenta desafíos éticos como resistencia al cambio, limitaciones técnicas, el criterio de pensar que la IA reemplazará los roles de trabajo, siendo esto falso, ya que sería un complemento requiriendo a profesionales en el tema capaces de adaptarse a los cambios constante que presenta la industria audiovisual. Esta investigación busca analizar la incidencia de la inteligencia artificial en la producción de contenidos audiovisuales explorando que herramientas se utilizan y como estas mismas están transformando las etapas de preproducción, producción y postproducción. Permitiendo identificar que oportunidades que ofrece la IA para poder mejorar los procesos, así como examinar los desafíos y limitaciones que surgen en su implementación. Además, permite reflexionar sobre el futro en la industria y determinar habilidades y conocimientos necesarios para adaptarse y aprovechar al máximo estas tecnologías.
Keywords: INTELIGENCIA ARTIFICIAL; AUTOMATIZACION; INDUSTRIAL AUDIOVISUAL